THU0490 Temporal increases in side effect concerns of osteoporosis medications among women with previous fractures. (12th June 2018) - Danila, M.I.; Rahn, E.J.; Mudano, A.S.; Outman, R.C.; Li, P.; Redden, D.T.; Anderson, F.A.; Greenspan, S.L.; LaCroix, A.Z.; Nieves, J.W.; Silverman, S.L.; Siris, E.S.; et al.
Abstract : Background: High-consequence, albeit rare, adverse side effects of osteoporosis medication raise patients' risk perceptions and contribute to non-adherence. In the past decade, fears of osteonecrosis of the jaw (ONJ) and atypical femoral fractures (AFF) have been increasingly reported as barriers to both the initiation of and adherence to osteoporosis medications. Objectives: To examine the temporal prevalence of self-reported concern about ONJ and AFF as reason for discontinuation of osteoporosis medication. Methods: Activating Patients at Risk for OsteoPOroSis (APROPOS) enrolled US women from the Global Longitudinal Study of Osteoporosis (GLOW) with previous self-reported fractures and no current use of osteoporosis medication. Using mailed surveys in 2010 (T1), 2012 (T2) and 2013 (T3), women were asked whether they discontinued osteoporosis medication in the prior year because of concerns about ONJ at three time points (T1, T2, T3) and AFF at two time points (T2, T3). We calculated the proportion of women reporting fears of ONJ and AFF among those who discontinued osteoporosis medication, and compared the proportions using chi-square tests. Results: A total of 833 women discontinued osteoporosis treatment at three time points, T1 (n=255), T2 (n=471), and T3 (n=107), respectively. There were no differences in the demographic characteristics between groups. The proportion of women reporting concerns of ONJ was 18.4% (T1), 26.7% (T2) and 64.5% (T3), while 23.5% (T2) and 60.7% (T3) reported fear of AFF as reason to discontinue osteoporosis treatment. These differences were statistically significant (p<0.0001) for all comparisons. Conclusions: The proportion of women reporting concerns of ONJ and AFF increased over time among those women who discontinue osteoporosis medications. Strategies are needed to help patients balance risks and benefits given a significant and temporally growing concern of rare bisphosphonate side effects. Disclosure of Interest: M. I. Danila: None declared, E. Rahn: None declared, A. Mudano: None declared, R. Outman: None declared, P. Li: None declared, D. Redden: None declared, F. Anderson Grant/research support from: Portola, Consultant for: Millennium Pharmaceuticals, S. Greenspan Grant/research support from: Amgen, Lilly, Consultant for: Merck, A. LaCroix Consultant for: Amgen, Pfizer, Sermonix, J. Nieves: None declared, S. Silverman Grant/research support from: Amgen, Lilly, Consultant for: Amgen, Speakers bureau: Amgen, Lilly, E. Siris Consultant for: Amgen, Radius, N. Watts Shareholder of: OsteoDynamics, Grant/research support from: Shire, Consultant for: AbbVie, Amgen, Janssen, Merck, Radius, Sanofi, Paid instructor for: Amgen, Shire, S. Ladores: None declared, K. Meneses: None declared, J. Curtis Grant/research support from: Amgen, Consultant for: Amgen, K. Saag Grant/research support from: Amgen, Lilly, Merck, Consultant for: Amgen, Lilly, Merck